Survival differences of low‐grade versus high‐grade head and neck pleomorphic dermal sarcomas and a review of a scalp case. Issue 1 (18th April 2022) - Janz, Tyler A.; Long, Barry D.; Joshi, Rohan R.; Coblens, Orly M.
Abstract: Objective: To examine survival by tumor grade of pleomorphic dermal sarcomas (PDS) of the head and neck (H&N) and review a scalp PDS case. Methods: Patients in the Surveillance, Epidemiology, and End Results (SEER) database were included from 1980 to 2016 based on a diagnosis of H&N PDS. Survival estimates were performed using Kaplan–Meier analysis. Additionally, a case of a grade III H&N PDS is presented. Results: Two hundred‐seventy cases of PDS were identified. The mean age at diagnosis was 75.1 years (SD: 13.5). Two hundred‐thirty‐four (86.7%) patients were male. Eighty‐seven percent of patients received surgery as a part of their care. The 5‐year overall survival rates for grades I, II, III, and IV PDSs were 69%, 60%, 50%, and 42%, respectively ( P = 0.03). Conclusions: H&N PDS occurs most commonly in older‐age males. Surgical management is frequently a part of H&N PDS care. Survival rates significantly decline based on tumor grade. Abstract : Survival rates by grade of pleomorphic dermal sarcomas of the head and neck. Key points: Pleomorphic dermal sarcomas are rare tumors of the head and neck. PDSs Predominantly affect Caucasian, older‐aged males and often present as high‐grade lesions. Surgery is the primary treatment modality used. Histological grade is an important factor when counseling patients. Survival rates for high‐grade PDSs are poor.